Using the Quality Control to Determine the Factors of Failure Operation in Cement Sector - Rashid, Kawa M. Jamal; Hama, Sherzad Arif (Sulaimani Journal for Pure and Applied Sciences, 2021)
Quality control technic is an important method of designing a strategic plan for many productive industries. The Shewhart control chart is that it uses only the information observation. Cumulative sum (CUSUM) and Exponentially weighted moving average (EWMA) two very effective alternatives to the Shewhart control chart may be used when small process shifts are of interest. This paper discusses data on failure time of five cement mills in Sulaimani Mass cement factories, used, the reliability methods for analysis the failure time. The quality of the products manufactured in this factory has been estimated according to a quality control process through the use of specific control chart one of the chart Exponentially Weighted Moving Average (EWMA) chart. Whereas reliability concerns functioning under specified time. So, it can be said that the reliability is a relation between production with expected period time in quality. This study investigates the implementation of reliability and quality control. The findings indicate that factors that affecting the function of mills which will increase the failure rate of mills and lower their life span, through which quality of products will be affected.
Keywords: Quality Control; Exponentially Weighted Mowing Average (EWMA); Process Capability Indices